PENGARUH STIMULI PEMASARAN DAN KARAKTERISTIK KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN DI PASAR TRADISIONAL - Liswani, Edy; Wahyuningsih, Tri (Universitas muhammadiyah palembang, 2017)
This research is formulated whether or not there was a significant influence ofmarketing stimultion (product, price, and location) and consumerscharacteristics (social status and life style) toward puchase decision attraditional market. This research wes considered as an associative research inline with marketing stimulation and consumers characteristics towardpurchase decision. There were 16 indicators used in this research. Thepopulation of this research was all people who live in sukajadi district. Therewere 138 respondents as samples got through cluster samling technique. Thedata used in this research was primary data to collect the data, the researcherused multiple linear regression. the results showed that there wassimultaneous and partial influence of marketing stimulation (product, price,and place) and cosumers characteristics (social status and life style) towardpurchase decision at traditional market.